The making of a lady [videorecording (DVD)] - Smith, Richard Curson; Wilson, Lydia, 1984-; Roache, Linus, 1964-; Lumley, Joanna; Burnett, Frances Hodgson, 1849-1924
During her duties as a lady's companion, Emily meets her employer's nephew, Lord James Walderhurst. Accepting his marriage proposal, Emily finds solace in the company of Walderhurst's nephew and his glamorous wife, after Lord James leaves to rejoin his regiment. Emily, alone with the Osborns, increasingly comes under their control. She begins to fear for her life.